Antidepressant activity of Trigonella foenum leaves in Wistar albino rats - Nayak, Roopa P.; Adake, Prabhakar; K., Hafis T. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: To evaluate antidepressant activity of ethanolic extract of Trigonella foenum in animal models. Methods: A total of 60 healthy male Wistar albino rats weighing 220-250 grams were used and they were divided into 10 groups of 6 rats in each. First five groups (1st -5th) were evaluated by Forced Swim Test (FST) and remaining by Tail Suspension Test (TST). 1st group (control) received normal saline 10 mg/kg, 2nd group (standard) Imipramine 10 mg/kg and 3rd, 4th and 5th groups (test) respectively received Trigonella foenum leaf ethanolic extract [TFEE] in different doses 100 mg, 200 mg, and 400 mg/kg per orally for 14 days. They were evaluated for antidepressant activity using FST after 60 minutes of drug administration on 14th day. Similarly, remaining five groups (6th to 10th) received the same drugs and evaluated using TST after 60 minutes of drug administration. Duration of immobility was noted for six minutes for each rat. Results: One way ANOVA and Tukey Krammer test were used for statistical analysis. The immobility periods were expressed in mean±SD. The immobility period in FST were 207.16±28.7, 50.08±2.9, 46.14±1.2, 40.5±3.4 and 40.0±3.6 seconds respectively for control, standard and three test groups of TFEE (100/200/400 mg/kg). Similarly, immobility periods of 163.11±31.9, 125.03±11.2, 138.81±16.44, 138.16±12.65, 127.58±4.3 seconds were noted for TST for remaining six groups. It was found that TFEE possess statistically significant (p<0.05) antidepressant activity, as evidenced by decrease in the immobility time in both the tests when compared to control group. Conclusions: Present study results demonstrated that TFEE possess antidepressant property in experimental models of depression.